Seeing the Unheard: Heritage Learners of Spanish and Photo-Diary Pedagogy. Issue 4 (2nd October 2017) - Schwartz, Adam; Terry, Helen
ABSTRACT: In response to calls to increase Spanish language learners' awareness of the relationship among power, language, and status in their communities and inspired by participatory research techniques, this article reports on the implementation of a photo-diary project with heritage and L2 learners in a basic-level Spanish language course. Students took part in critical reflections and dialogues related to the status of local varieties of Spanish and Spanish-English bilingualism in their surrounding communities. For this project, objectives were twofold: to address the frequent disconnect in Spanish heritage learner contexts between the classroom and local Spanish-speaking communities and to engage all learners in crucial reflections on the socially constructed hierarchies of language use in their daily lives. We assert that culturally responsive pedagogical tools challenge students to acknowledge familial and community voices and reconsider those voices as culturally and historically authoritative.